Structure, metamorphism and tectonic setting of a gneissic terrane, the Sagan Afelata area, southern Ethiopia. - Gichile, Samuel. (University of Ottawa (Canada), 1991)
The Sagan-Afelata area, which extends east approximately 100 km from the Main Ethiopian Rift towards the Adola gold fields, is underlain by high-grade rocks, dominantly biotite and quartzofeldspathic gneiss. The gneissic rocks are characteristically of K-rich mineralogy and appear to form a Proterozoic supracrustal sequence rather than Archean basement as thought earlier. The gneissic rocks were subjected to at least three distinct phases of deformation. The first, D$\sb1$, to which probably several generations of structures are attributed, formed migmatitic layering then isoclinal folds that transposed the layers parallel to flat-lying regional foliation (S$\sb1$), during amphibolite to granulite facies metamorphism. The second, D$\sb2$, formed upright folds in S$\sb1$ and parallel layers with subhorizontal NNW to NNE trending axes, accompanied by amphibolite facies metamorphism that overprinted most rocks. D$\sb3$, resulted in local E-W trending, open, upright folds that are confined to the eastern part of the area. (Abstract shortened by UMI.)
Keywords: Geology.